Comparative study of the degradation rate of new and regenerated mineral oils following electrical stress. Issue 21 (5th November 2018) - Oumert, Leila Safiddine; Boucherit, Ahmed; Zafour, Amel Hadj‐Ziane; Fofana, Issouf
Abstract : The objective of this contribution was to study the behaviour of new and regenerated insulating oil used in power transformers under the influence of an electric stress. To estimate the degradation rate of the dielectric fluids, one thousand (1000) successive breakdowns were generated according to the IEC 60156 standard. The parameters such as dissipation factor (Tan δ ), resistivity, total acid number (TAN) and oil water content were measured and examined following IEC/ISO standards. Good correlations have been obtained between TAN/resistivity and Tan δ which might provide a 'picture' of the fluid condition. The dissolved oxidation products for the two dielectric fluids (after the application of electric breakdowns) was evaluated by Fourier‐transform infrared spectroscopy. The results obtained indicate that the degradation of the parameters is significant and confirms the influence of an alternative electric field (AC) on the new and regenerated oils. It was also suspected that inhibitors and antioxidants were removed from the oil after regeneration. Their concentration should therefore be monitored and replenished when necessary.